(untitled) (Global Business Management Review (GBMR), 2022)
The housing is one of the basic requirements for ensuring the well-being of the people’s life is always preserved. The National Housing Policy has been practiced through the implementation of the Third Malaysia Plan as the government’s efforts to ensure all people have their own homes. Based on The Third Malaysia Plan (1976-1980), one of the essential objectives of social in Malaysia development is to meet the needs of housing; especially the lower–income group savour the facilities of adequate housing. Therefore, the government should continue to emphasize the necessity of providing adequate housing, quality and affordable housing to meet the needs of the targeted group. Generally, a policy statement written into guidelines on actions to be undertaken to improve the welfare of society (King et al, 2000) and also the government’s action plan to improve the well-being of the country. In the context of housing, housing policy development seen as a way for the government to intervene to ensure sufficient housing supply to meet the demand for urban homeowners and fulfilling social responsibilities of government.